A Simply Constructed Overlapped Domain Decomposition Method for Solving Large Scattering Problems. Issue 7 (2nd October 2016) - Han, Kui; Nie, Zaiping; Wang, Yiling
ABSTRACT: In this article, a simply constructed overlapped domain decomposition method is presented for analyzing electromagnetic scattering from perfect electric conducting objects with limited memory. In contrast to the conventional overlapped methods, the buffer regions in this method are limited to only a single layer of jagged triangular mesh cells. Furthermore, the overlapped currents belonging to adjacent sub-domains are expanded into different linear combinations of basis functions and enforced to be equal by a continuity condition. Then, a well-posed linear system is obtained, and an inner-outer iteration scheme is employed to solve the sub-domain problems one after another. In this method, the number of extra unknowns only increases with artificial boundaries. Numerical examples are presented to investigate the accuracy and robustness of the proposed approach.